(untitled) (Research, Society and Development, 2024)
Unfortunately, few health professionals are familiar with the dental management of children with cleft lip and palate. That is to say, they are not sufficiently informed about the dental management and treatment of these children, there should be a protocol to refer them to the corresponding specialties and provide better care to these children. One of our objectives is to perform an exhaustive search of the literature on the dental management of early childhood patients with cleft lip and palate and to describe the dental specialties involved in the treatments to be followed, in order to make known the benefits of an integral dental management in patients with cleft lip and palate. For this reason, we have made a search of several articles in several databases such as PubMed, ELSEVIER, Scielo, Scopus among others, then the information of each article was tabulated and filtered in order to have the articles related to our study population and in the same way the articles that did not fulfill the inclusion criteria were not taken into account. Patients born with this malformation should be accompanied by several health specialists and various dental specialties in order to explain to the parents what could be the etiological factors and help them with referrals to each specialist in the area to improve the quality of life of the patient and family members.